Examining political efficacy among Malaysian voters: The role of traditional and new media - Syed Abdullah Idid, Syed Arabi; Ahmed, Ismail Sheikh Yusuf; Souket, Rizwanah (John Benjamins, 2017)
The technological advancement and political situations have dramatically impacted the way traditional and new media have played their role in society, especially in the political development of the country. Studying media use and credibility have been a major concern among scholars to understand audience perceptions and attitudes towards the media and their role in politics. This study investigated the level of media use and credibility among voters and their perception of political efficacy. Drawing on a nationwide quota sampling of 2030 respondents, the findings found voter perception on the media as credible, with the highest trust being on television, followed by newspapers and radio. Internet was found to be the least credible. A factor analysis performed on the political efficacy items extracted three dimensions: Voter Efficacy, Internal Efficacy and External Efficacy. The results of hierarchical regression suggested that traditional and new media use as well as media trust dimensions were significantly correlated with political efficacy but different media use and credibility contributed differently to the various efficacy dimensions. Implications and recommendations are further discussed.